Security Managers’ Perspectives on Challenges Facing Commercial Banks in Preventing Frauds in Nairobi City County, Kenya - Godana, Hillary; Mwangi, Samson Wokabi; Mwaeke, Panuel (Advances in Social Sciences Research Journal, 2022)
This paper uses data collected for an MA Thesis on Security Managers’ perspectives on challenges facing Commercial Banks in Preventing Frauds in Nairobi County, Kenya. The study was motivated by continued rise of frauds in commercial banks in the county, despite the extensive mitigation measures put in place to deter frauds. The study established the nature of frauds prevalent in Kenya commercial banks in Nairobi County, assessed the determinants of fraud in Kenya commercial banks, determined Bank Security Managers Capacity in fraud prevention, and finally examined Security Managers perceptions on the relationship between the existing preventive measures and emerging Bank fraud trends in Nairobi County, Kenya. The study was grounded by the Fraud Triangle concept and adopted a case study qualitative design. The main method of data collection was the interview. The study comprises of 50 respondents: 39 main respondents and 11 Key Informants. The census sampling Method was used to select respondents for the study. Data was transcribed and the transcriptions coded using NVIVO software. The study established three major types of frauds; Management frauds, Non-Management Frauds and Third Party Frauds, all said to be on an increase trend. According to this study fraud rates are higher at Nairobi County (90%), than at other counties (70%). Mobile and Internet banking frauds were found to be the new threats challenging commercial banks because by their very nature because of technological sophistication, were committed from geographical location including outside the country. The study established two major determinants of frauds; Fraudsters Perspectives and institutional related factors. Major fraudster’s perspectives include; condition under which people can rationalize their prospective crimes, opportunities to commit crimes, perceived suitability of targets for fraud, technical ability of the fraudster, the possibility and likelihood of the fraud being discovered and the nature of consequences. Institutional factors that influence fraud prevalence include; weak accounting and control systems, and ineffective internal audits. According to the study, technological sophistication has outsmarted many security managers in the banking sector, because of their technological skills gaps in Fraud forensics. Finally, the study established the relationship between existing preventive measures and emerging Bank fraud trends in Nairobi County. Major policy recommendations suggested to cut frauds at the nib include; benchmarking for best internationally recognized standards such as carrying out expected and unexpected audits, enforced internal controls, regular training of security managers, and review of commercial banks organogram that will place security managers at a position to police frauds perpetrated by management.